Cần gấp
Cho tỉ lệ thức
`(a^2 + b^2)/(c^2 + d^2) = (ab)/(cd)` với `a,b,c,d \ne 0` và `c \ne -d`
c/m : `a/b = c/d` hoặc `a/b = d/c`
Cần gấp
Cho tỉ lệ thức
`(a^2 + b^2)/(c^2 + d^2) = (ab)/(cd)` với `a,b,c,d \ne 0` và `c \ne -d`
c/m : `a/b = c/d` hoặc `a/b = d/c`
Giải thích các bước giải:
Ta có:
`(a^2+b^2)/(c^2+d^2)=(ab)/(cd)`
`=>(a^2+b^2)cd=(c^2+d^2)ab`
`=>a^2 cd+b^2 cd=c^2 ab +d^2 ab`
`=>ac .ad+bd . bc=ac . cb + db . da`
`=>ac .ad+bd . bc-ac . cb – db . da=0`
`=>(ac.ad-ac.cb)-(db.da-bd.bc)=0`
`=>ac.(ad-cb)-bd.(da-bc)=0`
`=>(ac-bd).(ad-cd)=0`
TH`1`
`ac-bd=0`
`=>ac=0+bd`
`=>ac=bd`
`=>a/b=d/c(ĐPCM)`
TH`2`
`ad-cd=0`
`=>ad=0+cd`
`=>ad=cd`
`=>a/d=c/d(ĐPCM)`
$\quad \dfrac{a^2 + b^2}{c^2 + d^2}=\dfrac{ab}{cd}$
$\Leftrightarrow cd(a^2 + b^2)= ab(c^2 + d^2)$
$\Leftrightarrow a^2cd + b^2cd – abc^2 – abd^2 = 0$
$\Leftrightarrow (a^2cd – abc^2) + (b^2cd – abd^2)= 0$
$\Leftrightarrow ac(ad – bc)+ bd(bc – ad)= 0$
$\Leftrightarrow (ad-bc)(ac – bd)= 0$
$\Leftrightarrow \left[\begin{array}{l}ad – bc=0\\ac – bd=0\end{array}\right.$
$\Leftrightarrow \left[\begin{array}{l}ad = bc\\ac = bd\end{array}\right.$
$\Leftrightarrow \left[\begin{array}{l}\dfrac ab =\dfrac cd\\\dfrac ab =\dfrac dc\end{array}\right.$